位移检测装置及其省电方法 (2017)
本发明公开了种位移检测装置及其省电方法，位移检测装置包括位移感测模块、输入模块、距离感测模块与处理模块，其中处理模块电性连接位移感测模块、输入模块以及距离感测模块。输入模块用以提供非接触操作位移检测装置。距离感测模块用以检测物体与位移检测装置之间的距离，并据以产生感测值。处理模块依据距离感测模块的感测结果，而选择性地控制位移感测模块与输入模块进行开启或关闭。其中，当感测值小于第预设值时，将开启位移感测模块；当感测值大于第二预设值时，将开启输入模块及关闭位移感测模块。 The present invention discloses a displacement detecting device including a displacement sensing module, an input module, a distance sensing module, and a processing module, and a power saving method thereof. The processing module is electrically connected to each module. The input module is used to supply non-contact operation. The distance sensing module is used to detect the distance between a body and the displacement detecting device, and then produces a sensing value. The processing module selectively control the displacement sensing module and the input module to be turned on or turned off according to the sensing result of the distance sensing module. The displacement detecting device turns on the displacement sensing module when the sensing value is less than a first d